Awareness Regarding Diabetes Mellitus among Clients Attending a Diabetes, Thyroid & Endocrinology Care Centre, Kupandole, Kathmandu - Shrestha, Pragya; Shrestha, Pragya; Neupane, Gita; Shakya, Priti (Journal of Karnali Academy of Health Sciences, 2023)
Background: Diabetes mellitus is the most common non-communicable disease and has emerged as a major health issue globally. It is a group of metabolic disorders caused by high blood sugar in the blood. The awareness of patients about their illness is considered as an important factor in controlling blood sugar and preventing complications through self-care management. The objective of the study was to find out the level of awareness regarding diabetes mellitus among clients. Methods: A descriptive cross-sectional study was conducted among 80 diabetic clients. The clients were selected by non-probability sampling technique. A semi-structured interview schedule was used to collect the data. It included the components of diabetes such as its meaning, risk factors, causes, clinical features, blood tests, complications, management, and preventive measures. Data were analyzed by using descriptive statistics with Statistical Package for Social Science (SPSS) version 20.0. Results: Majority (76.25%) of the clients were in the age group of 55–79 years, and 51.25% were female. Most of the clients (81.25%) had a history of diabetes for 1–15 years since the diagnosis. Sixty percent had adequate awareness regarding diabetes mellitus. Conclusion: Based on the findings, it is concluded that the awareness regarding diabetes among clients is inadequate. They have inadequate awareness of the causes of diabetes in terms of smoking, alcohol consumption, and advancing age. Unawareness of the causes leads to ignorance of preventive measures for diabetes and low quality of life among diabetic clients. So, an improved and well-structured continuing educational program for raising awareness of diabetes among diabetic clients is needed.